Experience of Resection and Anastomosis for Tracheal Stenosis in a Tertiary Care Public Sector Hospital - Ahmad, Tanveer; Mazcuri, Misauq; Malik, Shoaib; Ali, Nadir; Abid, Ambreen; Sikandar, Nazish (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To document etiological spectrum of tracheal stenosis and results of resection and primary anastomosis Methodology: This prospective study was conducted in the Department of Thoracic surgery, Jinnah Postgraduate Medical center, Karachi from July 2019 to July 2021. All patients presenting with tracheal stenosis, fit for surgical resection were included. Results: Study comprised of 36 patients with 24(66.7%) males and 12(33.3) females. Mean age was 22.675.8 (7-35) years. Symptom duration was 22.77±14.5 weeks (range 6-60). Twenty-eight (77.8%) were benign and 8(22.2%) were malignant. Benign strictures were seen more among males (22/24; 91.7%; p=0.005) and malignant in females (6/12; 50%; p=0.005). Stridor and dyspnea was the commonest presentation. Hemoptysis was seen in four patients with squamous cell carcinoma (p=<0.001).Tracheal stenosis occurred at C7–T1 in 12 (33.3%), at C6-C7 and C6-T1 in 8 (22.2%) each. Non-intubated anesthesia used in 16 (44.4%) patients; Cervical and cervico-sternal approach used in 28(77.8%) and 8(22.2%) cases, respectively. Post-operatively, luminal diameter increase was 8.89±2.3 mm. Tumor-free margins were obtained in all squamous cell carcinoma (p=<0.001) cases. On table extubation was successful in 34(94.4%). Commonest complications were restenosis 6 (16.6%) and anastomotic leaks with emphysema in 4(11.1%). Post-operative duration of stay was 13.3±9.37 days. One (2.8%) patient died due to respiratory failure. Another required permanent tracheostomy. Mechanical ventilation was required in 4 (11.1%) due to respiratory compromise (p=<0.001) and tracheomalacia. Conclusion: A multidisciplinary approach in the management of tracheal stenosis produces the best outcome in operable cases with low morbidity and mortality.